Sowiecka grupa dywersyjno–wywiadowcza „Arsenał” i jej działalność na ziemiach polskich (październik 1944–styczeń 1945) - Bednarek, Jerzy (Dzieje Najnowsze, 2016)
The Soviet Sabotage–Intelligence Group „Arsenal” and Its Activity on Polish Lands (October 1944–January 1945) The article deals with the activity of a special sabotage–Intelligence group of the Soviet NKGB, working under the cryptonym „Arsenal” and dropped in Central Poland in the autumn of 1944. The group’s fundamental task consisted of destroying „means of communication deployed by the opponent for transporting equipment, people, and ammunition” along the Łódź– Końskie rail line and the Piotrków Trybunalski–Radom arterial road. The realization of this task was considered strategic for an offensive of the 1st Belorussian Front. The article is based on 14 volumes of the „Arsenal” group documentation in the archive of the SBU State Archives in Kyiv. The documents in question include, i.a. personal files of agents working for the Ukrainian NKGB, who formed the group in question, and detailed operation material pertaining to its activity, including plans, dispatches, cryptograms, accounts, and reports by group members. These vast and unique sources make it possible to reconstruct the sabotage and Intelligence work performed by the concrete special group, including the disclosure of the personal data of its agents. In addition — and this is of particular importance — they facilitate following the specificity of the arrangement and organization of Soviet sabotage groups during the end stage of the war, when responsibility for their activity lay with the 4th Department of the NKGB. It is specifically interesting that the preserved material shows also the actual attitude of the Soviet authorities towards the Polish military Underground (both communist and pro–independence). Such documents unquestionably allow us to confront and supplement our state of knowledge about the scale of the sabotage and the methods deployed by the Soviet special services in occupied Poland during the Second World War.